Effect of repeated in vitro sub-culturing on the virulence of metarhizium anisopliae against helicoverpa armigera (Lepidoptera : Noctuidae) - Nahar, Pallavi B.; Kulkarni, Shuklangi A.; Kulye, Mahesh S.; Chavan, Santosh B.; Kulkarni, Girish; Rajendran, Armugham; Yadav, Priya D.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
The effect of repeated conidial sub-culturing of Metarhizium anisopliae on its virulence against Helicoverpa armigera (Hbner) was studied. The LT(50) observed against third instar larvae of H. armigera for the first sub-culture was 3.4 days; it increased to 4.5 and 5.6 days for the 20th and the 40th sub-cultures, respectively. The LT50 values after passage of the 40th sub-culture on H. armigera decreased to 4.4 and 3.7 days for the 40th (first in vivo) and the 40th (fifth in vivo) passages, respectively. Similarly, the LC(50) of M. anisopliae towards third instar larvae of H. armigera increased from the first sub-culture (0.17x10(4)) to (3.0x10(4)) for the 40th conidial transfers on potato dextrose agar and again decreased to 0.74x10(4) and 0.23x10(4) in the 40th (first in vivo) and the 40th (fifth in vivo) passage, respectively. Similar trends for LC(50) and LT(50) values were seen when sugarcane woolly aphid, Ceratovacuna lanigera Zehntner was used as a host. Significant variation in appressorium formation and cuticle-degrading enzyme production such as chitinase, chitin deacetylase, chitosanase and protease during subsequent sub-culturing and passage through H. armigera was observed. Though there was no effect on internal transcribed spacer (ITS) sequence pattern, interestingly, in randomly amplified polymorphic DNA (RAPD), significant differences in the band intensities and in the banding pattern for different sub-cultures of M. anisopliae were observed. As stable virulence towards the insect pest is desirable for commercialisation of a mycoinsecticide, such changes in virulence due to repeated in vitro transfer need to be monitored and minimised.
Keywords: appressorium formation; chitin deacetylase; chitinase; Helicoverpa armigera; in vitro sub-culturing; Lipase; Metarhizium anisopliae; Protease